Secondary abdominal pregnancy following rupture of bicornuate uterus in early third trimester: a case report and review of literature - Katke, Rajshree D.; Raina, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Rupture uterus in a nulliparous woman is generally associated with mullerian anomalies and can present with acute obstetric emergency. It is a rare event and generally occurs in first or second trimester. Rupture of rudimentary horn in third trimester is extremely rare and can have adverse outcome for both mother and foetus. We describe a 24 years old primigravida patient with 28 weeks of gestation who came to casualty in gasping condition. She was having acute abdominal pain and distension with circulatory shock. Patient was immediately intubated and resuscitative measures started in casualty. Clinical and ultrasound findings suggestive of abdominal pregnancy and possibility of rupture of one horn of bicornuate uterus with haemoperitoneum. As patient was very critical resuscitative measures started and immediate laparotomy revealed abdominal pregnancy with dead foetus and ruptured right rudimentary horn with part of placenta adherent to omentum which was excised along with excision of rudimentary horn and placenta. Timely laparotomy with aggressive resuscitative measures saved the patients life. This case is extremely rare presentation of abdominal pregnancy in early third trimester and highlights the importance of early diagnosis of abdominal pregnancies and its timely management.